THE IMPACT OF LEADERSHIP ON ESPORT TEAM PERFORMANCE - Ronny Trian Surbakti; Regina Deti; Nina Septina (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study explores the impact of leadership on team performance in competitive game situations. The purpose of the study is to understand the importance of effective leadership strategies to maximise team performance and team success. The study uses a combination of literature review and use SMARTPLS as measuring tools. Research results show that effective leadership has a positive impact on team performance in esports. The study concludes that leadership has a significant impact on esports team performance. An effective leadership style that focuses on psychological factors and the role of the coach contributes to better team cohesion, better communication, and better execution of strategy. This paper highlights the importance of customised leadership strategies that consider the unique challenges and characteristics of the esports industry.